Thermal expansion behavior and estimated total polarizations of lead zirconate titanate-lead nickel niobate ceramics - Muangjai Unruan (2018)
Thermal expansion properties of lead zirconate titanate-lead nickel niobate ((1 - x)PZT-xPNN, x = 0.1-0.5) ceramics were determined in the temperature range of approximately - 100 to + 450 °C by dilatometer thermal expansion measurement. The observed deviation from the straight line below a Burns-like temperature for all the compositions was interpreted as due to the contribution from the dynamic polarization fluctuations of the relaxor part of the compositions. The Burns temperature was determined and found to increase with increasing PZT concentration. The local polarization was calculated from the thermal expansion data. Various aspects of understanding the polarization behavior and other effects in this ferroelectric system were also examined and discussed. © 2010 Elsevier B.V.